2020
DOI: 10.1111/imj.14889
|View full text |Cite
|
Sign up to set email alerts
|

Practical management of inflammatory bowel disease patients during the COVID‐19 pandemic: expert commentary from the Gastroenterological Society of Australia Inflammatory Bowel Disease faculty

Abstract: The COVID‐19 pandemic, caused by the novel coronavirus SARS‐CoV‐2, has emerged as a public health emergency and challenged healthcare systems globally. In a minority of patients, SARS‐CoV‐2 manifests with a severe acute respiratory illness and currently there are insufficient data regarding the virulence of COVID‐19 in inflammatory bowel disease patients taking immunosuppressive therapy. This review aims to summarise the current literature and provide guidance on the management of inflammatory bowel disease (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…55 Because nutrition is also an emerging prognostic factor, early intervention and support are warranted. 56…”
Section: General Management For Ibd In Covid-19 Pandemicmentioning
confidence: 99%
“…55 Because nutrition is also an emerging prognostic factor, early intervention and support are warranted. 56…”
Section: General Management For Ibd In Covid-19 Pandemicmentioning
confidence: 99%
“…Major American gastroenterological societies have recommended postponing non‐emergency endoscopies and using personal protective equipment in emergency endoscopies 199‐201 . For IBD patients, it is recommended that immunosuppressive drugs be delayed until the symptoms of COVID‐19 have resolved; however, the recommended management for severe GI diseases is mainly focused on prevention and supportive measures (64, 202 ).…”
Section: Management Of Sars‐cov‐2 Patients With Gi Manifestationsmentioning
confidence: 99%
“…Al-Ani et al carried out a literature review to prescribe that IBD patients should desist from immune-suppressing medications until infection resolution 7 . Aysha et al reported that a sub‐group of IBD patients with mild COVID-19 disease initially presented with diarrhoea rather than respiratory symptoms, leading to delayed diagnosis 8 , while D’Amico also reported that diarrhoea is a common symptom of COVID-19 in IBD patients 9 . Neurath et al posed a question on the role of immunosuppression and immunomodulation on the COVID-19 outcome of IBD patients 10 .…”
Section: Introductionmentioning
confidence: 99%